Assessment of the Public Procurement Systems of the Republic of Kazakhstan and the Sovereign Wealth Fund Samruk-Kazyna - World Bank; OECD; European Bank for Reconstruction and Development; Islamic Development Bank; Asian Development Bank (World Bank, Washington, DC, 2020)
This report provides the results of the assessment of the Public Procurement system of the Republic of Kazakhstan using the Methodology for Assessing Procurement Systems (MAPS)1 and its various steps, including the validation process. Kazakhstan has a dual public procurement system, in which there are separate systems for a) the government procurement conducted by the general public administration and b) procurement conducted by Sovereign Wealth Fund Samruk-Kazyna, which accounts for the majority of public procurement spending. This MAPS assessment covers both. Due to the nature of the system, this MAPS assessment has to integrated parts and assessments of a) the government procurement system and b) of Samruk-Kazyna’s procurement system. This assessment report identifies key findings, lays out the strengths of the analyzed procurement systems and the remaining challenges, and provides a series of recommendations to address those challenges and allow for future improvement.